2000
DOI: 10.3184/030823400103166283
|View full text |Cite
|
Sign up to set email alerts
|

Heteroaromatization with ketene dithioacetals: Part I. Synthesis of some novel 5-amino-1-(1,3,4-thiadiazol-2-yl) and 1-(1,3,4-thiadiazin-2-yl)pyrazole-4-carbonitriles

Abstract: Ketene dithioacetals [5][6][7][8][9][10][11][12][13][14] are one of the most common starting materials for the synthesis of pyrazoles. The reactions of ketene dithioacetals 1a,b with thiocarbohydrazide or thiosemicarbazide in hot ethanol afford the corresponding pyrazole derivatives 2a-d, respectively (Scheme 1). In addition, the syntheses of 2a-d could also be achieved through hydrazinolysis or ammonolysis of pyrazolyldithio-carbonate 3a,b, Scheme 1.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…
In a continuation of our previous work 11,12 on the synthesis of pyrazole-dithiocarboxylates, we report here several new approaches to these derivatives.Diazotisation of p- [(5-methylisoxazol-3-yl)aminosulfonyl]aniline 1 followed by coupling with ethyl acetoacetate or ethyl benzoylacetate in ethanol in the presence of sodium acetate afforded the corresponding arylazo-β-ketoester derivatives 2a and 2b, Scheme 1.The structures of 2a and 2b were confirmed on the basis of elemental analyses and spectral data. 1 H-NMR spectra showed that the products 2a and 2b exist in DMSO-d 6 as an equilibrium mixture of three tautomeric forms 2A-C, Scheme 2, as 1 H-NMR for 2a revealed three signals for one proton at δ 7.66, 11.35 and 11.58 ppm where for 2b these signals appear at δ 7.55, 11.32 and 11.48 ppm.
…”
mentioning
confidence: 88%
See 1 more Smart Citation
“…
In a continuation of our previous work 11,12 on the synthesis of pyrazole-dithiocarboxylates, we report here several new approaches to these derivatives.Diazotisation of p- [(5-methylisoxazol-3-yl)aminosulfonyl]aniline 1 followed by coupling with ethyl acetoacetate or ethyl benzoylacetate in ethanol in the presence of sodium acetate afforded the corresponding arylazo-β-ketoester derivatives 2a and 2b, Scheme 1.The structures of 2a and 2b were confirmed on the basis of elemental analyses and spectral data. 1 H-NMR spectra showed that the products 2a and 2b exist in DMSO-d 6 as an equilibrium mixture of three tautomeric forms 2A-C, Scheme 2, as 1 H-NMR for 2a revealed three signals for one proton at δ 7.66, 11.35 and 11.58 ppm where for 2b these signals appear at δ 7.55, 11.32 and 11.48 ppm.
…”
mentioning
confidence: 88%
“…In a continuation of our previous work 11,12 on the synthesis of pyrazole-dithiocarboxylates, we report here several new approaches to these derivatives.…”
mentioning
confidence: 88%
“…When pyrazolylcarbothiohydrazide 155 was treated with formic acid or triethyl orthoformate, it gave 3-methylsulfanyl-1-(1,3,4-thiadiazolyl-2-yl)pyrazolo[3,4- d ]pyrimidin-4(5 H )-one 156 ( Scheme 80 ) [ 118 ].…”
Section: Heteroannulated Pyrazolesmentioning
confidence: 99%
“…[3] Ketene dithioacetals could be used in reactions with various nucleophiles leading to synthesis of a variety of nitrogen heterocycles like pyridines, pyridones, pyrimidines, quinolines, pyrroles, pyrazoles and imidazoles. [1,2,[5][6][7][8][9][10][11] They are used in the synthesis of sulfur containing heterocycles like thiophenes, thiopyrans and other bioactive molecules like cyclopentanoids, polyenes, etc. [1][2][3][4][5][6][7][8][9][10][11] Thiophenes form a major class of bioactive heterocycles.…”
Section: Introductionmentioning
confidence: 99%
“…[1,2,[5][6][7][8][9][10][11] They are used in the synthesis of sulfur containing heterocycles like thiophenes, thiopyrans and other bioactive molecules like cyclopentanoids, polyenes, etc. [1][2][3][4][5][6][7][8][9][10][11] Thiophenes form a major class of bioactive heterocycles. They show a broad spectrum of biological response such as antibacterial, [12][13][14] anti-leishmanial, [1] antifungal, [1,[12][13][14][15] antimicrobial, [12][13][14][15] antitumor, [16,17] anticancer, [16,17] antiinflammatory, [13,14] antiproliferative, [18] molluscicidal [19] and anticonvulsant activity.…”
Section: Introductionmentioning
confidence: 99%